(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The Kuhitang ridge is located in the south-western part of the Pamir-Alay Mountain range. Administratively, it belongs to the territory of Sherabad district of Surkhandarya region. The western slope of the Kuhitang ridge is the territory of the Republic of Turkmenistan, where the Kuhitang Nature Reserve (total area 27139 ha) is located [1, 2]. The total length of the border from south to north is about 70 km and is located at an altitude of 850-3137 m above sea level. The average height of the watershed is 2682 m in the north (Khatak section), 3137 m in the central part (Ayri Bobo peak of Kampirtepa section) and 2361 m in the southern part (Vandob section).